(untitled) (European Journal of Social Sciences, 2023)
We examined the level of stress, aggression, health anxiety and well-being and their changes in almost every wave of the pandemic, and we have reported about the results in national and international studies. In Wave V, the prolonged effect of the pandemic, and, over the mental situational picture, the population’s post-traumatic condition was also examined. Our current research is focusing on the situational picture of North-Hungary, our aim is to get know the mental state of the region’s population. During the research, we used the Mental Health Continuum Scale (MHC-SF), the Depression, Anxiety and Stress Scale (DASS-21) and the Post-traumatic Growth Inventory (PTGI) completed with background variables. Results: the questionnaire was filled by 482 persons living in the region, 34.4% of them were men, 65.6% were women, average age 33±15.1. The mental health of the region’s population appears to be below the average (x=32.6±11.8). The worst situation was found in the population’s social well-being (x=9.7±4.7) which did not reach the threshold value. The respondents’ average was in the normal range on the depression, anxiety and stress scale (x=21.9), but the more severe stage of depression was shown by 30% of the respondents, the same of anxiety by 29.5% and stress by 19.9%. The existence of the population’s post-traumatic condition could be detected in the region (x=43.1±20.9) that could be interpreted as the aftermath of the pandemic. The COVID infection occurring in the family has strongly influenced the development of the condition (p<0.009).